2000
DOI: 10.1002/1526-4998(200012)56:12<1029::aid-ps238>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

In vivo control andin vitro antifungal activity of rhamnolipid B, a glycolipid antibiotic, againstPhytophthora capsici andColletotrichum orbiculare

Abstract: The glycolipid antibiotic rhamnolipid B isolated from Pseudomonas aeruginosa strain B5 was evaluated for in vitro antifungal activity and in vivo control against phytophthora blight and anthracnose under glasshouse conditions. Rhamnolipid B showed antifungal activity against Cercospora kikuchii, Cladosporium cucumerinum, Colletotrichum orbiculare, Cylindrocarpon destructans, Magnaporthe grisea and Phytophthora capsici. Microscopic observation revealed that the high level of antifungal activity (10 mg ml À1 ) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
97
1
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(114 citation statements)
references
References 21 publications
10
97
1
6
Order By: Relevance
“…The application in storage was evaluated by assessment of disease severity (Kim et al, 2000). Mature and healthy red tomato (Lycopersicon esculentum cv.…”
Section: Application In Fruit Storagementioning
confidence: 99%
“…The application in storage was evaluated by assessment of disease severity (Kim et al, 2000). Mature and healthy red tomato (Lycopersicon esculentum cv.…”
Section: Application In Fruit Storagementioning
confidence: 99%
“…This is supported by the work of Calvo et al (2004) where it was reported that biosurfactants produced by microbes during growth on water-immiscible substrates, permit their growth on such substrates by reducing the surface tension thereby making the hydrophobic substrate more readily available for uptake and metabolism. Kim, Lee, and Hwang (2000) also found that very often, the growth of microorganisms on hydrocarbons is accompanied by the emulsification of insoluble carbon sources in the culture medium and in most cases has been attributed to the production of emulsifying agents in the presence of these substrates. Several authors have reported diesel oil and crude oil as excellent substrates for microbial growth and also for biosurfactant production (Ilori et al, 2005;Adebusoye, Ilori, Amund, Teniola, & Olatope, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…La actividad lítica de los bPP producidos por las cepas de P. fluorescens 021V y 039t sobre las zoosporas de P. infestans, se debe a su composición química que permite una afinidad con la membrana de la zoospora. Por lo cual el biosurfactante se puede intercalar entre la membrana plasmática y generar un desequilibrio en su integridad y permeabilidad, provocando ruptura de la membrana y liberación del contenido citoplasmático (stanghellini y Miller, 1997; Kim et al, 2000;Martínez y osorio, 2007). sin embargo, aunque es posible que el efecto de los biosurfactantes sobre las zoosporas pueda reducirse por el enquistamiento natural que ocurre en las zoosporas después de 2 h para la formación de la pared celular, estos productos pueden continuar reduciendo la infección de P. infestans, ya que estudios de Kim et al (2000) en P. capsici, De Jonghe et al (2005 en P. cryptogea, y Martínez y osorio (2007) en P. infestans, han demostrado que los ramnolípidos también tienen efecto inhibitorio sobre otras estructuras con pared celular del patógeno.…”
Section: Actividad Zoosporicida De Los Bppunclassified
“…Lo anterior orienta a que los biosurfactantes y/o las suspensiones bacterianas de P. fluorescens productoras de biosurfactantes deben estar presentes antes de la llegada del patógeno, para que ejerzan un mecanismo de acción preventivo mediante la reducción de la concentración de inóculo (Jonghe et al, 2005;Kim et al, 2000).…”
Section: Actividad Biocontroladora De Los Bpp Y De Las Cepas De P Flunclassified
See 1 more Smart Citation